Murder at the taffy shop - Day, Maddie (Day, Maddie. Cozy Capers Book Group mystery., 2021)
When her friend Gin, the owner of a taffy shop, is accused of murdering a wealthy genealogist, Cape Cod bicycle shop owner Mac Almeida must unwrap the clues with the help of the Cozy Capers crime solvers to solve this sticky case.